Implementasi Teknologi IoT pada Aplikasi Pencarian Lokasi Calon Penumpang dan Angkutan Umum (Studi Kasus Koperasi Bina Usaha Transportasi Republik Indonesia) - Putri Kamaliyah Kirana Dewi; Pikir Wisnu Wijayanto; Bayu Rima Aditya (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity was carried out to respond to the decline in public interest in public transportation due to concerns about crime, limited route information and uncertainty about departure times. In addition, income inequality between transportation owners and drivers also exacerbates the problem of clarity of information. This activity focuses on applying Internet of Things (IoT) technology to overcome these problems by developing a location search application for prospective public transport passengers. This application utilizes Bluetooth Low Energy (BLE) devices as an IoT technology. BLE devices are installed on public transport vehicles to enable real-time location tracking. BLE technology was chosen because of its low energy consumption, adequate communication range, and ability to interact with users' mobile devices. Users' information collected by BLE devices is sent to a central server, which then processes and presents the data to users via a mobile application. The main objective of this activity is to develop and evaluate IoT-based applications. The methodology includes descriptive and qualitative approaches, with data collection techniques through observation, interviews and documentation studies. The results of implementing IoT technology in location search applications show significant benefits. This application increases the efficiency of public transport management by providing real-time information regarding routes and departure schedules. Additionally, customer satisfaction increases as passengers can better plan their trips. The app's "Emergency Call" feature also "helps reduce crime-related concerns and improves passenger safety. The app also provides easily accessible route information and transparency regarding drivers' daily earnings, helping minimize income inequality.